Vacancies and interstitials in yttrium. (5th March 2019) - Borodin, V A; Vladimirov, P V
Abstract: The paper deals with the first principles simulation of formation energies and migration barriers of self point defects, including vacancies, di-vacancies and single interstitial atoms, in metallic yttrium. The vacancy formation energy in yttrium is shown to be relatively high (~1.8 eV), whereas the migration barriers are very similar for the jumps inside the basal planes and between basal planes, being equal to ~0.65 eV. The sum of these numbers reasonably reproduces the experimental values of the self-diffusion activation barriers. The vacancy pairs at the first nearest neighbor separation (divacancies) have binding energy of ~0.2 eV, which is only weakly sensitive to the divacancy orientation in the lattice, whereas vacancy pairs at the second and third nearest-neighbor separations are energetically unfavorable, suppressing the dissociation of divacancies. Together with the noticeably lower divacancy migration barriers with respect to single vacancies, this makes divacancies efficient mediators for mass transfer in Y. Among multiple possible configurations of a single interstitial, only the basal octahedral one is found to be the true energy minimum, while all the other considered possibilities are either unstable, or saddle points on the potential energy surface. This is in contrast to other hcp metals, where several metastable interstitial configurations often coexist. The lowest migration barriers for single interstitial diffusion along the basal plane and between planes are practically equal, ~0.4 eV, implying isotropic diffusion of interstitials in yttrium. Overall, the predicted properties of point defects in yttrium are in line with the general trends for hcp metals with the c / a ratio below .